Pulmonary Vein in a Pinch - Muhab Saadeh; Ayham Mahmoud; Mahmoud Ma’aita; Asal Eiadeh; Ayman Hammoudeh; Mousa Saadeh; Moath Said Alfawara (Methodist DeBakey Cardiovascular Journal)
The pulmonary veins normally drain into the left atrium, with the superior pulmonary veins typically situated anterior and inferior to the right pulmonary arteries. However, anomalies can happen. We encountered an exceedingly rare pulmonary vascular anomaly for a patient presenting with atypical chest pain, where the right superior pulmonary vein aberrantly ran posterior to the right pulmonary artery (RPA) and became compressed between the RPA and the right main bronchus. Coronary computed tomography angiography identified this specific pulmonary vein anomaly but revealed unremarkable coronary arteries.